A catalog of the Hybotidae of Chile (Diptera: Empidoidea) - González, Christian R.; Elgueta, Mario; Ale-Rocha, Rosaly (Zootaxa, 2021)
A catalog of the Hybotidae of Chile is provided. We present all valid names and synonyms for the 27 species and 10 genera distributed in the country, including information about name, author, year of publication, page number, type species, type depository, type locality and references. The geographical distribution of the species was recorded from bibliographic data and revised collections. Two species previously recorded for the Hybotidae fauna of Chile must be deleted: Drapetis armipes Bezzi, described from Tacna – Peru, and Ocydromia philippii Bigot, a synonym junior of Hyperperacera nemoralis (Philippi), now in Brachystomatidae (Trichopezinae). Bicellaria collina (Philippi) and Austrodromia? valdiviana (Philippi) are maintained in Hybotidae waiting for clarification of correct taxonomic assignment.